Quantum size luminescence effect in local field enhancement of Ag NP added Er3+ glass system - Sutrisno, M. S.; Naaim, M. M.; H., Nurhafizah; Sazali, E. S.; Zaid, M. H.M.; Malek, M. F.; Hisam, R. (Elsevier, 2024)
This research investigates the effect of silver (Ag) addition on the photoluminescence enhancement properties of 20Li2O–5Bi2O3-(74-x)TeO2–1Er2O3-xAg glass samples, aiming to optimize luminescence for applications in optical amplifiers and laser technologies. The enhancement of luminescence properties for both upconversion 4S3/2 → 4I15/2 green band and 4F9/2 → 4I15/2 red peak luminescence observed are analyzed by quantum yield ξ and relative intensity enhancement (I/Io) parameters. The enhancement on green luminescence properties are observed with high ξgreen and I/Iogreen at x < 1 mol% which can be explained within the cavity quantum electrodynamics (CQED) framework due to very low dipolar localized surface plasmon mode volume Veff (∼10–20 × 10−22 m3) allowing stronger quantum size luminescence effect. Meanwhile, the quenching of ξgreen (0.61) at x ≥ 1 mol% may indicate the weaker quantum size luminescence effect. An anomalous enhancement on red luminescence properties with high ξred (2.07) and I/Iored (1.79) at x = 1.25 mol% cannot be explained by CQED framework but from phonon-assisted energy transfer (PET) mechanism occurred due to structural changes. The near-field and far-field parameters of AgNP are simulated. Results demonstrated stronger near field electric field distribution enhancement at x = 0.5 mol% and x = 0.75 mol%. This suggests that an optimal AgNP radius exists for promoting the quantum size luminescence effect in our glass samples, falling within the range of 50.00–60.00 nm. Further supporting this conclusion, theoretical calculations using light intensity scattering efficiency (Qsca) revealed the highest values between 50.00 and 70.00 nm of AgNP radius in our glass samples.